CT Features of Parotid Gland Oncocytomas: A Study of 10 Cases and Literature Review - Tan, T.J.; Tan, T.Y. (American Journal of Neuroradiology, 2010)
SUMMARY: Oncocytomas of the salivary glands are rare benign epithelial tumors which occur most commonly in the parotid gland. The aim of our study was to characterize the clinical-radiologic-pathologic spectrum of parotid oncocytomas in a series of 10 cases seen in our institution between January 2003 and November 2008. The CT features of parotid oncocytomas in the largest imaging series of this rare but important benign lesion include a well-defined enhancing tumor with a “deformable” appearance when large, and a non-enhancing curvilinear cleft or cystic component. These CT findings are potentially helpful in distinguishing these benign lesions from other parotid tumors in clinical scenarios that preclude surgical resection or when biopsy results are non-diagnostic. Further studies are advocated to validate the specificity and positive predictive value of these imaging features.